Uji Sitotoksik Ekstrak Biji Pare (Momordica charantia L.) pada Kultur Sel Limfosit T Pasien LES In Vitro - Permana, Galih Indra; Balgis, .; Mujosemedi, . (Nexus Biomedika, 2013)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease, mediated by lymphocytes. Wrong regulation in immune system causes autoreactivity of T lymphocytes and hyperactivity of B lymphocytes then causes inflammation in site organ. Extract of bitter melon seeds contains ribosome inactivating proteins (RIPs), momordin I, and momordin II which can induce apoptosis in the cells and have cytotoxic effects. This study is to examine the cytotoxic effects of bitter melon seeds extract on cultured T lymphocytes of SLE patient in vitro. Methods: This study was an experimental laboratory research with posttest control group design. Sample was culture of T lymphocytes from SLE patient with the active phase. T lymphocytes culture was divided in four groups that were bitter melon seeds extract, cyclophosphamide, control media, and control cells. Cytotoxic effects were measured with MTT assay then the data were analyzed with statistical regression analysis to determine the IC50. Results: IC50 of bitter melon seeds extract on culture of T lymphocytes cell of SLE patient was 1704.07 µg/ml and normal sample was 19.20 µg/ml. While IC50 of cyclophosphamide for treatment of SLE sample was 16.80 µg/ml and for normal sample was 39.24 µg/ml. Extract of bitter melon seeds had weak cytotoxic effect on T lymphocyte cell culture of SLE patient and moderately active cytotoxic effect on T lymphocyte cell culture of normal sample. Conclusion: Extract of bitter melon seeds had weak cytotoxic effects on T lymphocyte cell culture of SLE patient with IC50 was 1704.07 µg/ml. Keywords: SLE, bitter melon seed extract, cytotoxic, lymphocytes T